Pain catastrophizing: An historical perspective. Issue 1 (March 2017) - Neblett, Randy
Abstract: Pain catastrophizing has become an in increasingly popular subject in pain research. It has been found to be associated with self‐reported pain severity, depressive and anxiety symptoms, and disability. This construct is an important component of the well‐established, and continually evolving, Fear‐Avoidance Model of Chronic Pain . More recently, a Communal Model of Pain Catastrophizing has been proposed. The concept of pain catastrophizing has an interesting history. This article discusses the origins, various definitions, and conceptual evolution of the catastrophizing in clinical evaluation and research.